A systematic pan-cancer analysis of the gasdermin (GSDM) family of genes and their correlation with prognosis, the tumor microenvironment, and drug sensitivity - Zheng, Yufu; Yuan, Didi; Zhang, Fei; Tang, Renkuan (Frontiers in Genetics, 2022)
Background: Pyroptosis is a programmed cell death process mediated by the gasdermin (GSDM) protein. However, limited research has been conducted to comprehensively analyze the contribution of the GSDM family in a pan-cancer setting. Methods: We systematically evaluated the gene expression, genetic variations, and prognostic values of the GSDM family members. Furthermore, we investigated the association between the expression of GSDM genes and immune subtypes, the tumor microenvironment (TME), the stemness index, and cancer drug sensitivities by means of a pan-cancer analysis. Results: GSDM genes were highly upregulated in most of the tested cancers. Low-level mutation frequencies within GSDM genes were common across the examined types of cancer, and their expression levels were associated with prognosis, clinical characteristics, TME features, and stemness scores in several cancer types, particularly those of the urinary system. Importantly, we found that the expression of GSDMB, GSDMC, and GSDMD was higher in kidney carcinomas, and specifically kidney renal clear cell carcinoma (KIRC); which adversely impacted patient outcome. We showed that GSDMD was potentially the most useful biomarker for KIRC. The drug sensitivity analysis demonstrated that the expression of GSDM genes were correlated with the sensitivity of tumor cells to treatment with chemotherapy drugs nelarabine, fluphenazine, dexrazoxane, bortezomib, midostaurin, and vincristine. Conclusion: GSDM genes were associated with tumor behaviors and may participate in carcinogenesis. The results of this study may therefore provide new directions for further investigating the role of GSDM genes as therapeutic targets in a pan-cancer setting.